Los órganos autónomos e independientes (2003)
In our constitutional order, there are institutions whose origin is quite different some ones stand because there is a formal constitutional determination. Others, by the contrary, have its origin in law. Autonomy and independence are qualities of constitutional institutions: these are limited only by Constitution itself. Institutions born by law, are limited by legislator . Our last constitutional reform –1991- created two different kinds of institutions: some ones, like great orders, embracing minor institutions : Electoral Council and National Control body